PATTERN OF DEFOLIATION AND ITS EFFECT ON PLANT PERFORMANCE AND BIOMASS PARTITIONING IN ABELMOSCUS ESCULENTUS - Dasti, Altaf A.; Saima, Shehzadi; Imtiaz, Aysha; Fatima, Kaniz; Malik, Saeed A. (Journal of Research (Science), 2004)
Three experiments were performed to examine the effect of defoliation on plant performance and biomass partitioning among different plant modules. Different patterns of tissue removal were used to simulate natural herbivore damage in Abelmoscus esculentus (L.). Plants were subjected to removal of tissues from either a single leaf or throughout the plant. The effect of defoliation on plant performance and biomass allocation was quantified by using Classical Growth Analysis Technique. Both levels of defoliation and patterns of tissue removal effect growth performance of Abelmoscus esculentus. Temporal compensatory changes in relative growth rate were mediated by similar changes in net assimilation rate (NAR). The ontogenetic changes in leaf area ratio (LAR) to defoliation were largely determined by changes in specific leaf area (SLA) rather than leaf weight ratio (LWR) during the experimental period. All defoliation treatments show initial shifts of biomass from leaves to stems and roots but eventually reached to the level of control (un-defoliated) plants with the passage of time i.e. they show compensatory changes.